Profil Kemampuan Berpikir Kritis Murid Fase D dalam Menyelesaikan Soal Cerita Materi Tabung melalui Pembelajaran Mendalam - Annisa' Ibtihal (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
This study aimed to describe the profile of Phase D students critical thinking skills in solving word problems on cylinder material through deep learning. The research was conducted because many students still encountered difficulties in interpreting word problems, selecting appropriate solution strategies, evaluating the accuracy of their answers, and formulating conclusions logically. Through deep learning, students were expected to develop their critical thinking skills more effectively. This study employed a descriptive qualitative approach. The participants were 28 students of class IX B at SMP Negeri 1 Rambipuji. Data were collected through critical thinking skills tests, observations, and interviews. The indicators of critical thinking skills examined in this research included interpretation, analysis, evaluation, and inference. Seven students were selected as subjects, two students from the high category, three students from the moderate category, and two students from the low category. Students with high critical thinking skills demonstrated strong abilities in understanding problems, determining suitable solution strategies, evaluating the correctness of their work, and drawing logical conclusions. Students with moderate critical thinking skills were generally able to analyze problems and identify solution strategies, although they still made errors in calculations and evaluating their answers. Meanwhile, students with low critical thinking skills experienced difficulties in understanding problems, selecting appropriate strategies, evaluating solutions, and making accurate conclusions. The student worksheet and digital learning media used in this study were designed according to deep learning principles. Students were trained to interpret, analyze, evaluate, and draw inferences from contextual problems relevant to their daily lives. They also presented their work and engaged in peer evaluation. These deep learning experiences supported the development of students critical thinking skills, as reflected in their ability to successfully solve word problems test.
:: Finalisasi file repositori 21 Juli 2026_Kurnadi
Keywords: kemampuan berpikir kritis; pembelajaran mendalam; soal cerita; tabung; murid fase d